High genetic diversity in American chestnut (Castanea dentata) despite a century of decline - Sophia S. Stoltz; Brian C. Husband (Conservation Genetics, 2023)

The origins and evolutionary history of feral apples in southern Canada - Dane Cronin; Paul Kron; Brian C. Husband (Molecular Ecology, 2020)
Feral populations of domesticated crops can establish through two nonmutually exclusive pathways: hybridization with native relatives and recruitment of and recombination between known cultivars. The extent and relative importance of these pathways is not known, especially for woody fruit crops. Here, we examined the evolutionary origins of feral populations of Malus domestica (domestic apple) in southern Canada using a population genetic analysis. We characterized genotypes of 578 putative feral apple trees and evaluated them in relation to genotypes of 156 commercial cultivars, 28 non‐native, ornamental crabapples and 47 native Malus coronaria trees using 14 microsatellite markers. No feral trees were genetic admixtures between domestic and native Malus ; however, a minority of trees were admixed with introduced ornamental Malus . Feral trees and commercial cultivars both occurred in two major genetic groups and seven subgroups distributed throughout all commercial growing regions. A total of 42 cultivars, both heritage and currently grown, occurred in probable parental pairs for feral trees, with nine heritage varieties accounting for 72% of parental assignments. We conclude that feral apples in southern Canada are not products of hybridization with native M. coronaria but we cannot exclude ornamental apple species as contributing to the naturalization process. Nonhybrid feral domestic apples have multiple origins, with a prominent signature of early heritage cultivars. These lineages have spread and coexist throughout Ontario, rather than being derived strictly from local sources.

Understanding the spectacular failure of DNA barcoding in willows ( Salix ): Does this result from a trans‐specific selective sweep? - Diana M. Percy; George W. Argus; Quentin C. Cronk; Aron J. Fazekas; Prasad R. Kesanakurti; Kevin S. Burgess; Brian C. Husband; Steven G. Newmaster; Spencer C.H. Barrett; Sean W. Graham (Molecular Ecology, 2014)
Willows ( Salix : Salicaceae) form a major ecological component of Holarctic floras and consequently are an obvious target for a DNA ‐based identification system. We surveyed two to seven plastid genome regions (~3.8 kb; ~3% of the genome) from 71 Salix species across all five subgenera, to assess their performance as DNA barcode markers. Although Salix has a relatively high level of interspecific hybridization, this may not sufficiently explain the near complete failure of barcoding that we observed: only one species had a unique barcode. We recovered 39 unique haplotypes, from more than 500 specimens, that could be partitioned into six major haplotype groups. A unique variant of group I (haplotype 1*) was shared by 53 species in three of five Salix subgenera. This unusual pattern of haplotype sharing across infrageneric taxa is suggestive of either a massive nonrandom coalescence failure (incomplete lineage sorting), or of repeated plastid capture events, possibly including a historical selective sweep of haplotype 1* across taxonomic sections. The former is unlikely as molecular dating indicates that haplotype 1* originated recently and is nested in the oldest major haplotype group in the genus. Further, we detected significant non‐neutrality in the frequency spectrum of mutations in group I, but not outside group I, and demonstrated a striking absence of geographical (isolation by distance) effects in the haplotype distributions of this group. The most likely explanation for the patterns we observed involves recent repeated plastid capture events, aided by widespread hybridization and long‐range seed dispersal, but primarily propelled by one or more trans‐species selective sweeps.

The association between polyploidy and clonal reproduction in diploid and tetraploid Chamerion angustifolium - Sarah J. Baldwin; Brian C. Husband (Molecular Ecology, 2013)
Clonal reproduction is associated with the incidence of polyploidy in flowering plants. This pattern may arise through selection for increased clonality in polyploids compared to diploids to reduce mixed‐ploidy mating. Here, we test whether clonal reproduction is greater in tetraploid than diploid populations of the mixed‐ploidy plant, Chamerion angustifolium, through an analysis of the size and spatial distribution of clones in natural populations using AFLP genotyping and a comparison of root bud production in a greenhouse study. Natural tetraploid populations (N = 5) had significantly more AFLP genotypes ( = 10.8) than diploid populations ( = 6.0). Tetraploid populations tended to have fewer ramets per genotype and fewer genotypes with >1 ramet. In a spatial autocorrelation analysis, ramets within genotypes were more spatially aggregated in diploid populations than in tetraploid populations. In the greenhouse, tetraploids allocated 90.4% more dry mass to root buds than diploids, but tetraploids produced no more root buds and 44% fewer root buds per unit root mass than diploids. Our results indicate that clonal reproduction is significant in most populations, but tetraploid populations are not more clonal than diploids, nor are their clones more spatially aggregated. As a result, tetraploids may be less sheltered from mixed‐ploidy mating and diploids more exposed to inbreeding, the balance of which could influence the establishment of tetraploids in diploid populations.

The effects of rapid desiccation on estimates of plant genome size - Jillian D. Bainard; Brian C. Husband; Sarah J. Baldwin; Aron J. Fazekas; T. Ryan Gregory; Steven G. Newmaster; Paul Kron (Chromosome Research, 2011)

Soil microbial communities from an elevational cline differ in their effect on conifer seedling growth - Cameron Wagg; Brian C. Husband; D. Scott Green; Hugues B. Massicotte; R. Larry Peterson (Plant and Soil, 2011)

Spatial patterns of plant diversity below‐ground as revealed by DNA barcoding - PRASAD R. KESANAKURTI; ARON J. FAZEKAS; KEVIN S. BURGESS; DIANA M. PERCY; STEVEN G. NEWMASTER; SEAN W. GRAHAM; SPENCER C. H. BARRETT; MEHRDAD HAJIBABAEI; BRIAN C. HUSBAND (Molecular Ecology, 2011)
Our understanding of the spatial organization of root diversity in plant communities and of the mechanisms of community assembly has been limited by our ability to identify plants based on root tissue, especially in diverse communities. Here, we test the effectiveness of the plastid gene rbcL , a core plant DNA barcoding marker, for investigating spatial patterns of root diversity, and relate observed patterns to above‐ground community structure. We collected 3800 root fragments from four randomly positioned, 1‐m‐deep soil profiles (two vertical transects per plot), located in an old‐field community in southern Ontario, Canada, and extracted and sequenced DNA from 1531 subsampled fragments. We identified species by comparing sequences with a DNA barcode reference library developed previously for the local flora. Nearly 85% of sampled root fragments were successfully sequenced and identified as belonging to 29 plant species or species groups. Root abundance and species richness varied in horizontal space and were negatively correlated with soil depth. The relative abundance of taxa below‐ground was correlated with their frequency above‐ground ( r = 0.73, P = 0.0001), but several species detected in root tissue were not observed in above‐ground quadrats. Multivariate analyses indicated that diversity was highly structured below‐ground, and associated with depth, root morphology, soil chemistry and soil texture, whereas little structure was evident above‐ground. Furthermore, analyses of species co‐occurrence indicates strong species segregation overall but random co‐occurrence among confamilials. Our results provide insights into the role of environmental filtering and competitive interactions in the organization of plant diversity below‐ground, and also demonstrate the utility of barcoding for the identification of plant roots.

Pollinator-mediated assortative mating in mixed ploidy populations of Chamerion angustifolium (Onagraceae) - Brad F. Kennedy; Holly A. Sabara; Dan Haydon; Brian C. Husband (Oecologia, 2006)

Sexual interference within flowers of Chamerion angustifolium - Matthew B. Routley; Brian C. Husband (Evolutionary Ecology, 2006)

Effects of a belowground mutualism on an aboveground mutualism - Benjamin E. Wolfe; Brian C. Husband; John N. Klironomos (Ecology Letters, 2005)
Studies of multitrophic interactions between below‐ and aboveground communities have generally focused on soil organisms and antagonists of plant shoots and leaves (herbivores). Despite the widespread occurrence of plant mutualists below‐ and aboveground which can occur on the same host plant, the potential for interactions between them has not been considered. Here we demonstrate that aboveground plant mutualists, insect pollinators, are strongly influenced by belowground plant mutualists, arbuscular mycorrhizal fungi. The presence of arbuscular mycorrhizal fungi in the roots of Chamerion angustifolium increased pollinator visitation and per cent seed set of this plant in the field by up to two times compared with non‐mycorrhizal plants. We propose that interactions between belowground and aboveground mutualisms are widespread and may play important functional roles in populations and communities.

Relationship between the abundance ofLythrum salicaria (purple loosestrife) and plant species richness along the Bar River, Canada - Michael A. Treberg; Brian C. Husband (Wetlands, 1999)